Preliminary Results from the Yala-Xiangbo Leucogranite Dome, SE Tibet - Aikman, Amos B; Harrison, T Mark; Lin, Ding (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp.91